How Significant is Africa's Demographic Dividend for Its Future Growth and Poverty Reduction? - Ahmed, S. Amer; Cruz, Marcio; Go, Delfin S.; Maliszewska, Maryla; Osorio-Rodarte, Israel (World Bank, Washington, DC, 2014)
Africa will be undergoing substantial demographic changes in the coming decades with the rising working age share of its population. The opportunity of African countries to convert these changes into demographic dividends for growth and poverty reduction will depend on several factors. The outlook will likely be good if African countries can continue the gains already made under better institutions and policies, particularly those affecting the productivity of labor, such as educational outcomes. If African countries can continue to build on the hard-won development gains, the demographic dividend could account for 11 to 15 percent of gross domestic product volume growth by 2030, while accounting for 40 to 60 million fewer poor in 2030. The gains can become much more substantial with even better educational outcomes that allow African countries to catch up to other developing countries. If the skill share of Africa's labor supply doubles because of improvements in educational attainment, from 25 to about 50 percent between 2011 and 30, then the demographic dividends can expand the regional economy additionally by 22 percent by 2030 relative to the base case and reduce poverty by an additional 51 million people.